การใช้ประโยชน์เปลือกและกากมันสำปะหลังในการผลิตก๊าซชีวภาพ - ยุวดี มาทอง (จุฬาลงกรณ์มหาวิทยาลัย, 2016)
This research aims to study potential to produce biogas from peel and pulp from cassava starch industry. Preliminary potential of biogas production from the solid wastes was investigated by BMP method. Biogas production efficiency improvement by either pretreatment with 3% sodium hydroxide (NaOH) solution or co-digestion of peel or pulp with waste water from the cassava starch production process was also comparatively studied. The study found that single substrate fermentation of either pulp or waste water produced high biogas production potential with 0.601 and 0.589 m3/kg VS added respectively. While the peel produced only 0.306 m3/kg VS added, but increased up to 0.400 m3/kg VS added or only 31% increasing after pretreatment with 3% NaOH solution for 48 h. The result of co-digestion between pulp and waste water, peel and waste water, or peel and pulp showed no significant potential increasing of the biogas production. Hence, it can be concluded that both solid wastes and waste water from the cassava starch industry have high potential for biogas production. It also showed that the cassava pulp can be utilized to produce biogas directly without pretreatment of co-digestion. While utilizing the cassava peel as a co-substrate with either pulp or waste water is one more alternative for the solid waste management even though the peel produced lower potential of biogas production than the pulp and waste water from the production process.